COULD HERBAL MEDICINE BE A COMPLEMENTARY THERAPY IN LEUCORRHEA TREATMENT AND CARE? - Zubaeda Zubaeda; Nur Khafidhoh (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: The frequency of using the antibiotics and antifungals as a treatment of leucorrhea may cause the bacterial and fungal resistance. Therefore, a treatment is not always optimal and sometimes leads the infection to be worsen. The herbal medicine is needed as an alternative treatment. This study aims to examine the effectiveness of using various herbal medicine in the management of leucorrhea. Methodology: The literature review was conducted in several electronic databases i.e., Google Scholar, Science Direct, and PubMed. The protocol for this study was PRISMA. The keywords such as